KAJIAN KEBERLANJUTAN PENGELOLAAN EKOWISATA BERBASIS DAERAH PERLINDUNGAN LAUT (DPL) DI PSISIR DESA BAHOI, MINAHASA UTARA, SULAWESI UTARA - Andronicus, Andronicus; Yulianda, Fredinan; Fahrudin, Achmad (JEMIS (Journal of Engineering & Management in Industrial System), 2016)
This study aimed to assess sustainability status of coastal ecotourism management of Bahoi village , North Minahasa , North Sulawesi -based marine protected area ( MPA). The result of this study reveals that Rapfish method, may be used as a method on appraising sustainability status of coastal resource management. Rapid Appraisal of Coastal Ecotourism analysis show that sustainability index of Bahoi village is 52,47. Thus sustainability status of coastal ecotourism management of Bahoi village is sustainable. Monte Carlo analysis method shows that indices from Rapid Appraisal of Coastal Ecotourism analysis are stable.